A randomized double-blind active-controlled clinical trial on the efficacy of topical basil (Ocimum basilicum) oil in knee osteoarthritis - Askari, Alireza; Hasheminasab, Fatemeh Sadat; Sadeghpour, Omid; Naghizadehd, Mohammad Mehdi; Ravansalar, Seyed Ali; Iraji, Aida; Hashempur, Mohammad Hashem (Frontiers in Pharmacology, 2024)
Background Basil is a widely used herb in Persian medicine and is gaining recognition as a functional food worldwide. Aim of the study This trial aimed to assess the effectiveness of a traditional formulation of basil oil in comparison with diclofenac gel in treating knee osteoarthritis, considering its established anti-inflammatory, anti-nociceptive, and anti-oxidative properties. Materials and methods One hundred eligible patients were equally randomized to the traditional basil oil (containing sesame oil) and diclofenac gel groups. They used their respective topical treatments thrice daily for 4 weeks. Various measurements were taken at the beginning of the study, 2, and 4 weeks after starting the intervention, including the 8-m walk test, knee pain (based on visual analog scale), flexion angle of the knee joint, analgesic consumption, and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. Results No significant differences were observed between the basil oil and diclofenac gel groups in any of the measured outcomes. However, significant improvements were noted within each group for most variables. Conclusion Topical application of the traditional formulation of basil oil appears to improve clinical symptoms and certain functional indicators of knee osteoarthritis to a similar extent as diclofenac gel. This suggests that basil oil could be considered an effective management option for this condition. Clinical Trial Registration:https://irct.behdasht.gov.ir/, identifier IRCT2017081711341N7.